Bioactive Compounds and Health Benefits of Wasabi (Eutrema Japonicum): Antibacterial, Cytotoxic, and Anti-inflammatory Properties of Root and Leaf Extracts - Daniella, Rafaella; Wang, Wenbin; Hellman, Bernhard; Suryoprabowo, Steven (International Journal of Food Sciences and Nutrition Innovations, 2025)
Background of study: Eutrema japonicum, commonly known as wasabi, is a perennial plant native to Japan and a member of the Brassicaceae family. Traditionally used as a pungent condiment in Japanese cuisine, wasabi has garnered scientific interest for its wide array of bioactive compounds with potential therapeutic properties. While its rhizome (commonly referred to as the "root") is the primary component used in culinary applications, recent studies suggest that both the root and leaf extracts may serve as sources of valuable phytochemicals with health-promoting effects. Aims and scope of paper: The aim of this study is to investigate and compare the antibacterial, cytotoxic, and anti-inflammatory properties of root and leaf extracts of Wasabi (Eutrema japonicum), with a focus on identifying key bioactive compounds responsible for these biological activities. The study seeks to evaluate the therapeutic potential of both plant parts to support their application in functional foods, nutraceuticals, or natural health products. Methods: This review aims to find scientific evidence in order to support claims related to Eutrema japonicum. As a consequence, it is very important to gather studies related to the functional properties of butterfly pea from scientific research. Result: The study revealed that both root and leaf extracts of Eutrema japonicum (wasabi) are rich in key bioactive compounds, including isothiocyanates, phenolics, and flavonoids, which underlie their biological effects. The root extract showed notably stronger antibacterial effects, along with greater cytotoxicity toward human cancer cell lines such as HeLa, MCF-7, and A549. Although the root was more biologically active overall, the leaf extract also demonstrated promising therapeutic potential. These results highlight the value of both plant parts as potential sources of functional ingredients for the development of nutraceutical and pharmaceutical applications. Conclusion: This study highlights the significant health-promoting properties of Eutrema japonicum (wasabi) through the evaluation of its root and leaf extracts. Both plant parts were found to be rich in bioactive compounds, particularly isothiocyanates, phenolics, and flavonoids, which are responsible for their observed antibacterial, cytotoxic, and anti-inflammatory activities.